2019
DOI: 10.1111/andr.12694
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bisphenol A exposure on DNA integrity and protamination of mouse spermatozoa

Abstract: Background Bisphenol A is widely used in the manufacture of polycarbonate plastics and has caused increasing concern over its potential adverse impacts on spermatogenesis. However, the effect of bisphenol A on spermiogenesis is yet to be explored. Objectives To evaluate whether bisphenol A has adverse effects on DNA integrity and protamination of spermatogenic cell. Materials and methods Newborn male mice were subcutaneously injected with bisphenol A (0.1, 5 mg/kg body weight, n = 15) or coin oil (control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…The diminished sperm count after BPA exposure was confirmed by several other studies in rodents [83,91,[94][95][96][97][98][99] and humans [76,100]. Lower levels of exposure were also associated with reduced sperm motility [83,94,95,97,101,102] and acrosomal integrity [94], impaired markers of OS [83,94,95,97], and increased DNA fragmentation indexes [21,25,95,97,[101][102][103][104] in animal models. In humans, several epidemiologic studies also reported a negative association between urinary BPA levels and sperm concentration, total sperm count [76], motility, and viability [31,76,79,[105][106][107], but not with morphology [100].…”
Section: Bpa-induced Alterations In Testicular Structure Function Asupporting
confidence: 66%
“…The diminished sperm count after BPA exposure was confirmed by several other studies in rodents [83,91,[94][95][96][97][98][99] and humans [76,100]. Lower levels of exposure were also associated with reduced sperm motility [83,94,95,97,101,102] and acrosomal integrity [94], impaired markers of OS [83,94,95,97], and increased DNA fragmentation indexes [21,25,95,97,[101][102][103][104] in animal models. In humans, several epidemiologic studies also reported a negative association between urinary BPA levels and sperm concentration, total sperm count [76], motility, and viability [31,76,79,[105][106][107], but not with morphology [100].…”
Section: Bpa-induced Alterations In Testicular Structure Function Asupporting
confidence: 66%
“…Studies on human subjects and animals have consistently shown a correlation between exposure to BPA and the reproductive system, such as decreased fertility, impaired sperm function, low sperm count, and increased morphological sperm abnormalities (Pan et al, 2020). Leydig cell growth and function and related reproductive disorders such as testicular dysgenesis, delayed puberty, and subfertility/infertility is associated with BPA exposure (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…D.pan et al findings identified that bisphenol A exposure may negatively contribute to the sperm quality in adult mice. Mechanistically, we showed that bisphenol A reduced sperm chromatin integrity along with increased DNA damage, which may be due to poor protamination of spermatozoa [56].…”
Section: Metabolism and Toxicokineticsmentioning
confidence: 84%